Compressive and shear strengths of coir fibre reinforced activated carbon stabilised lateritic soil - Tamassoki, Sakina (MDPI, 2022)
Constructing structures on lateritic soil is challenging in geotechnical engineering due to the various physical and geotechnical characteristics. Many studies investigated different stabiliser materials to strengthen the geotechnical parameters of lateritic soil. This study used activated carbon and coir fibre (ACF) to stabilise lateritic soils as an environmentally friendly binder. Experiments including the unconfined compressive strength (UCS) test and the direct shear test (DST) are performed to investigate the mechanical properties of ACF-stabilised soil for different percentages of activated carbon (AC). Before and after ACF stabilisation, microstructural characterisations of soil samples were performed using field emission scanning electron microscopy (FESEM) and surface-area analysis (BET). The experimental results demonstrate that 3% ACF can considerably enhance the compressive strength, while 2% ACF significantly improves the shear strength, of lateritic soil. Accordant to the UCS results, using fibre in AC-stabilised soil improves post-peak behaviour and residual strength. Moreover, 2% ACF can significantly improve shear strength by creating an interlocking matrix among AC, soil particles, and fibre. The microstructural characterisation based on the findings obtained by FESEM and BET analysis confirms that AC particles fill soil voids. AC restrains the soil movement when exposed to external stresses. In addition, the formation of gel in the stabilised soil matrix binds the soil particles, increasing the strength of the ACF-stabilised soil in comparison with untreated soil.